THE EFFECT OF WORKLOADS AND COMPENSATION ON WORK MOTIVATION IN SASMITA JAYA FOUNDATION - Harras, Hadyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The complexity of motivational problems has always been an obstacle to employee performance. Therefore, it is important to do research on the causal factors. To answer this problem, quantitative approaches and regression analysis are used. The population in this study were 70 employees of Sasmita Jaya Foundation and the sample technique used was census. The results prove that workload has a significant effect on work motivation with a regression coefficient of 0.569. Compensation has a significant effect on work motivation with a regression coefficient of 0.478. Simultaneous analysis prove that workload and compensation have a significant effect on work motivation with a determination coefficient of 72.5%, while the remaining 27.5% is explained by other variables outside of this study